Draft Annual Plan 1987-88 Volume : III General Areas Government of Assam - Planning Commission (Planning Commission, 1987)
The Karbi Langpi(Lower Borpani) H.E. Project in the district of Karbi Anglong of Assam was sanctioned in September 1979 at an estimated cost of Rs. 36.36 Crores Including the transmission component of Rs. 2.21 crores the Project comprises of the construction of a 51 metre high concrete dam on the river Borpani near Hatidubi for utilising the inflows from a catchment area of 1178 Sq. Km. This diverted water will be carried through a low pressure tunnel of 4.2. metres via, 4430 metres long, a surge shaft, two steel liners and penstocks of 2.6 meters and 755 metres in length to the Dower Borpani Power House with an installation of 2x50MW Hydro Electric Generating units for Utilising the average Head of 240 metres.
Government of Assam, Planning and Development Department